Improving Drilling Skills in Football Games Through The Happy to Play Mini Plastic Ball in Class VII.3 SMP Negeri 9 Kendari - Syamsu Alam Syamsu Alam (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This study aims to improve dribbling skills in soccer games for class VII students through the habit of playing with mini plastic balls. This research was conducted in the 2018/2019 school year's odd semester at SMPN 9 Kendari for class VII students. 3, totaling 36 students. This type of research is Classroom Action Research (CAR) using qualitative and quantitative research approaches (mixed methods research design). Data analysis used includes qualitative and quantitative data analysis. The results showed that in the first cycle, the observations scored 119, meaning that the skills of dribbling the ball in the student's soccer game were quite good. However, the researcher will carry out cycle II to be even more conducive to dribbling skills in student soccer games. In cycle II the observation results showed a score of 164, meaning that the skills of dribbling the ball in the student soccer game were excellent. In student observation activities, the teacher assesses that students can adjust the power of kicks, use the inside or outside of the feet, adjust body balance, focus their views, and control the ball.